ASOSIY VOSITALAR HISOBINI TASHKIL QILISHNING INNOVATSION TRANSORMATSIYASI (Multidisciplinary Journal of Science and Technology, 2025)
This scientific article presents innovative methodological approaches and tools for organizing the accounting of fixed assets for enterprises engaged in production activities.